Environmental Degradation due to Tobacco Cultivation in Northern Bangladesh (The Dhaka University Journal of Earth and Environmental Sciences, 2021)
A field study was conducted in Northern Bangladesh, Rangpur district to observe the impact of tobacco cultivation on the environment as well as to characterize contributing factors motivating tobacco cultivation. Information was collected from the tobacco cultivators by a questionnaire survey that was conducted in four mostly tobacco cultivated upazilas, namely Badargonj, Taragonj, Rangpur Sadar, Gangachara of Rangpur district. Information from non-tobacco cultivators was also collected from Mithapukur Upazila. Survey findings revealed that 62.16% of respondents believed that soil productivity is decreasing in the tobacco field and 70.27% of tobacco farmers were using more chemical fertilizer per year than the previous years. More than half (54.05%) of respondents reported that tobacco is replacing native food crops. Moreover, 51.30% of tobacco farmers were facing various health hazards due to tobacco cultivation. The present study also investigated that 97.14% of farmers got a high benefit along with 89.19% of respondent’s availed organizational support from tobacco marketing companies. The overall satisfaction rate with the price was 80.56%, which was the main contributory factor for tobacco cultivation in the study area. The survey results also identified that farmers from Mithapukur Upazila gave up tobacco cultivation due to health hazards and unnecessarily underestimating the grade of tobacco leaf by the buyer company.The Dhaka University Journal of Earth and Environmental Sciences, Vol. 9(2), 2020, P 19-26